Intersection of Artificial Intelligence in a Multi-Religious Nation: A Sociological Perspective - Omosomuofa Obruche (dialektika kontemporer, 2026)
Religious belief and practice are among the many facets of human life that artificial intelligence is progressively influencing. Both opportunities and obstacles arise when integrating artificial intelligence with Christian traditions in Nigeria, where religion is strongly embedded in the social and cultural life of the people. With an emphasis on its use in biblical interpretation, sermon preparation, and church practice, this study investigated the sociological ramifications of artificial intelligence for Christian religiosity in Delta State. Using a qualitative design, the study employed sociological and historical methods because they are considered germane for document analysis, thematic interpretation, and semi-structured interviews. Twenty participants, including pastors, lecturers, religious students, and lay members actively utilising artificial intelligence tools, were selected through a purposive sampling process. Secondary literature on artificial intelligence and religion was used to supplement field data. The results showed that artificial intelligence tools, including Bible apps, translation software, and digital concordances, are useful for improving exegesis, sermon preparation, and scriptural accessibility. However, serious theological and ethical issues surfaced. As lay members increasingly consult artificial intelligence tools on their own, respondents emphasised the dangers of plagiarism, an excessive dependence on technology, the distortion of sacred meaning, and challenges to pastoral authority. There were clear generational differences: elder clergy highlighted the limitations of artificial intelligence, especially in areas of spiritual discernment, while younger Christians were more open to the technology. The study concludes that while artificial intelligence can democratise access to the Bible and enhance biblical studies, it must continue to be used in conjunction with divine inspiration and human-centred interpretation. In addition to highlighting more general sociological issues about authority, authenticity, and religion in a quickly digitising society, the study emphasises the necessity of ethical frameworks to direct the use of artificial intelligence in religious contexts. To better comprehend this changing junction, suggestions are given for more extensive comparative studies across Nigerian regions and religious traditions.